Strategic reading 3 : - Richards, Jack C. (Cambridge University Press, 2003)
Strategic Reading is a three-level series designed to develop reading, vocabulary-building, and critical-thinking skills. The Student's Book contains 16 thematic units with a selection of engaging topics that motivate learners to relate the reading to their own experiences